A statistical jacobian application for power system optimization of voltage stability - Raja Masood Larik; Mohd. Wazir Mustafa; Manoj Kumar Panjwani (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Despite a tremendous development in optimal power flow (OPF), owing to the obvious complexity, non-linearity and unwieldy size of the large interconnected power systems, several problems remain unanswered in the existing methods of OPF. Seizing specific topics for maximizing voltage stability margin and its implementation, a detailed literature survey discussing the existing methods of solution and their drawbacks is presented in this research. The phenomenon of voltage collapse in power systems, methods to investigate voltage collapse, and methods related to voltage stability are briefly surveyed. Finally, the study presents a statistical method for analyzing a power system through eigenvalue analysis in relation to the singular values of the load flow Jacobian. Future study may focus on changes in theories in conjunction with large power systems.